Analisis Pengaruh Penerapan Good Corporate Governance terhadap Tobin's Q dan Return On Equity (ROE) - Jessica, . (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2007)
During 1997-1998 most of Asian Countries including Indonesia has severe a financial crisis. This crisis is happened because of the poor implementation of good corporate governance. Theoretically, the benefit of implementation of the good corporate governance are increase corporate value, reduce risk that caused by conflict of interest among owners and management, and finally good corporate governance can increase investor trust.